Thermo-mechanical behavior simulation and cracking risk evaluation on steel-concrete composite girders during hydration process. (October 2021) - Zhang, Zejun; Liu, Yongjian; Liu, Jiang; Zhang, Ning
Abstract: Due to the temperature and volume changes caused by hydration heat, shrinkage, and creep, early-age concrete in steel-concrete composite girder bridges often have cracks even before the bridge opening to the traffic. In this study, thermo-mechanical behavior and concrete cracking risk in composite girders were investigated by field measurements and finite element models (FEM). Firstly, temperature field model and mechanical behavior model were established in sequence and verified by the measured data of temperature and strain. According to the FEM, the influence of interfacial stiffness on axial stress of the early-age concrete deck was studied, and proved to be nonnegligible. As for the steel girder, the influence of interfacial stiffness on the axial stress can be ignored except for the steel-concrete interfacial region near the end section of girders. Among temperature, shrinkage, and creep, temperature dominates the axial stress with the proportion of about 85% of the coupling axial stress (sum of the stress of temperature, shrinkage, and creep). The shrinkage effect causes tensile stress in concrete with a small proportion of about 3%. For creep effect, it causes opposite stress state in tension and compression with temperature in concrete deck. Finally, parametric studies involving initial temperature, curing temperature and the thickness of concrete deck were performed to evaluate the cracking risk of early-age concrete under different seasons. The result shows that, to avoid concrete cracking, concrete casting for a deck thinner than 0.2 m can be conducted without any curing method. While for the deck with a thickness from 0.2 m to 0.4 m, the concrete casting without any curing method should be conducted during specific period. For a deck thicker than 0.4 m, effective curing method must be used during concrete casting.